Pulmonary thromboembolism in hospitalised patients with COVID-19: a retrospective national study of patients managed in critical care and ward environments in Scotland - Ninian N Lang; Michael McGettrick; Catherine Bagot; M K Johnson; Alistair Colin Church; Alexander MacLellan; Paul McCaughey; Melanie J Brewis (BMJ Open)
Objectives To assess for increase in pulmonary thromboembolism (PTE) in hospitalised patients with COVID-19, in both critical care and ward environments.Setting We reviewed all CT pulmonary angiograms (CTPA) performed in Scotland between 23 March 2020 and 31 May 2020 and identified those with COVID-19 using either classical radiological appearances or positive COVID-19 PCR swab.Participants All hospitalised patients in Scotland with COVID-19 between 23 March 2020 and 31 May 2020 who underwent a CTPA.Primary outcome measure To assess if the rate of PTE was increased in those with COVID-19 compared with previously published figures of hospitalised patients.Secondary outcome measures To assess the effect of right heart strain or requirement for critical care on mortality.Results 3401 CTPAs were reviewed. 192 were positive for PTE in patients with evidence of COVID-19 either real-time PCR swab positive for SARS-CoV-2 (n=104) or having radiological changes consistent with COVID-19 (n=88). The total number of hospital admissions in Scotland between 23rd March 2020 and 31st May 2020 with COVID-19 was 5195. The incidence of PTE during this time was 3.7% in all patients admitted to all hospitals in Scotland with COVID-19 during this period. 475 hospitalised patients were managed in critical care (both level 2 and level 3 care), in whom the incidence of PTE was 6% (n=29). 4720 patients did not require admission to critical care, in whom the incidence of PTE was 3.5% (n=163). There was increased risk of death with right heart strain (25/52 vs 128/140 (p<0.01)) and in critical care (15/29 vs 146/163 (p<0.01)).Conclusions We have demonstrated an increased risk of PTE in critical care and ward-based environments. Further studies are required to establish effective prophylactic anticoagulation in this group.